Prevention of cold injuries during exercise - Castellani, J. W.; Young, A. J.; Ducharme, M. B.; Giesbrecht, G. G.; Glickman, E.; Sallis, R. E. (Medicine & Science in Sports & Exercise, 2006)
It is the position of the American College of Sports Medicine that exercise can be performed safely in most cold-weather environments without incurring cold-weather injuries. The key to prevention is use of a comprehensive risk management strategy that: a) identifies/assesses the cold hazard; b) identifies/assesses contributing factors for cold-weather injuries; c) develops controls to mitigate cold stress/strain; d) implements controls into formal plans; and e) utilizes administrative oversight to ensure controls are enforced or modified. The American College of Sports Medicine recommends that: 1) coaches/athletes/medical personnel know the signs/symptoms and risk factors for hypothermia, frostbite, and non-freezing cold injuries, identify individuals susceptible to cold injuries, and have the latest up-to-date information about current and future weather conditions before conducting training sessions or competitions; 2) cold-weather clothing be chosen based on each individual's requirements and that standardized clothing ensembles not be mandated for entire groups; 3) the wind-chill temperature index be used to estimate the relative risk of frostbite and that heightened surveillance of exercisers be used at wind-chill temperatures below -27 degrees C (-18 degrees F); and 4) individuals with asthma and cardiovascular disease can exercise in cold environments, but should be monitored closely.